1993
DOI: 10.1080/09544829308914787
|View full text |Cite
|
Sign up to set email alerts
|

General Framework for Configuration Design: Part 1— Methodology

Abstract: Configuration design is a type of conceptual design activity in which physical systems are synthesized from a set of predefined components that can be combined only in certain ways. A general framework for automated configuration of systems is presented in this paper. In this framework, design specifications are separated into functions, performance goals and constraints. Starting with design specifications, a skeletal design comprising essential functions is first configured. The process of mapping functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Several approaches to circuit con guration design have been developed using arti cial intelligence. Kota and Lee (1993a) describe a functional reasoning-based approach to the con guration of power transmission systems. The outcome of this work was the development of a knowledgebased system with seven functional modules required to represent the uid power domain: energy conversion, motion actuation, power distribution, power regulation, sensing, power storage, and contamination (Kota and Lee 1993b).…”
Section: Design Approaches In Uid Power Designmentioning
confidence: 99%
“…Several approaches to circuit con guration design have been developed using arti cial intelligence. Kota and Lee (1993a) describe a functional reasoning-based approach to the con guration of power transmission systems. The outcome of this work was the development of a knowledgebased system with seven functional modules required to represent the uid power domain: energy conversion, motion actuation, power distribution, power regulation, sensing, power storage, and contamination (Kota and Lee 1993b).…”
Section: Design Approaches In Uid Power Designmentioning
confidence: 99%
“…Ecological assessments of new materials are typically not carried out until after material development [8] where their impact on the material decisions may be minimal. Studies have shown for example, that 70% of product life cycle costs result from design phase decisions, which are settled on early in product development [9]. Likewise, environmental impact could similarly become fixed as a result of early design phase decisions.…”
Section: Introductionmentioning
confidence: 98%
“…Because of this, function-to-structure mapping is also referred to as 'catalogue lookup approach' (Chandrasekaran 1990) or 'catalogue-driven approach' (Gui and Mäntylä 1994). For example, Kota and Lee (1993) have developed a function decomposition and function-to-structure mapping framework to design hydraulic systems. They use two building blocks for the mapping: Functional Building Block (FBB) and Structural Building Block (SBB).…”
Section: Introductionmentioning
confidence: 98%